2013
DOI: 10.4067/s0716-97602013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole (BTH) induces resistance to Pepper golden mosaic virus (PepGMV) in pepper (Capsicum annuum L.)

Abstract: SUMMARYPepper is an economically important crop in many countries around the world but it is susceptible to many diseases. In Mexico, diseases caused by bipartite begomoviruses have emerged as important problems in pepper. Several control strategies have been explored wiht little success; most of them are based on the avoidance of virus transmission and the breeding for resistance. Abiotic inducers can act at various points in the signaling pathways involved in disease resistance, providing long-lasting, wide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…These results are in agreement with those reported by Trejo-Saavedra et al [40] in pepper crops infected with begomoviruses or those reported in tomato infected with Cucumber mosaic virus [50]. Our results strongly suggest that the observed hypersusceptibility is due to the absence of SA, as it can be reverted by BTH.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with those reported by Trejo-Saavedra et al [40] in pepper crops infected with begomoviruses or those reported in tomato infected with Cucumber mosaic virus [50]. Our results strongly suggest that the observed hypersusceptibility is due to the absence of SA, as it can be reverted by BTH.…”
Section: Discussionsupporting
confidence: 94%
“…Based on previously reported BTH concentrations for foliar treatments in different plants including tomato [3840], 1 mM BTH treatments were employed. This concentration had no visible effect on plant development in Money Maker plants and prevented the necrotic phenotype of NahG plants, which were grown at high light conditions for correct viroid replication [14].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, resistance was induced in pepper plants against PepGMV infection. Pepper plants treated with BTH were characterized for resistance depending on symptom appearance, virus accumulation and viral movement (Trejo-Saavedra et al, 2013).…”
Section: Similar Work Have Also Been Demonstrated In Tobacco Andmentioning
confidence: 99%
“…Most studies showing efficient activity of chemical SAR activators follow spray application of the chemicals. The spraying of solution ranging in concentrations of 0.5 mM to 1 mM has shown positive results (Kessmann et al, 1994;Gorlach et al, 1996;Conrath et al, 1995;Trejo-Saavedra et al, 2013).…”
Section: Application Of Chemical Sar Activatorsmentioning
confidence: 99%
“…Previously, it has been reported that pepper plants subjected to biolistic inoculation with Pepper golden mosaic virus (PepGMV, Begomovirus) and treated with Benzothiadiazole (BTH) showed a 5-6-fold reduction in viral concentration compared to the untreated plants (Trejo-Saavedra et al, 2013). In the present study, an approximately 4-fold reduction in viral concentration was obtained for tomato plants that received inoculations with ToSRV and ToCV at 45 DAT and subjected to the pretreatment and biweekly sprayings compared to the viral concentration in untreated plants (Figure 1).…”
Section: Resultsmentioning
confidence: 99%